Life expectancy and business cycles in a small open economy - Tselmuun Tserenkhuu; Stephen Kosempel (Osaka University, Institute of Social and Economic Research (ISER), 2024)
This paper examines the effects of increased life expectancy on the short-run macroeconomic stability of a typical small open economy. We develop a real-business-cycle (RBC) model of a small open economy that is consistent with the main empirical facts of economic fluctuations in open economies. Different from the previous satisfactory open-economy extensions of the baseline RBC model, given its finite lifetimes feature, our framework also helps rationalize some of the key results from recent empirical literature on the relationship between longevity and business cycles. In our model, changes in life expectancy change the planning horizon of individuals and thus affect their intertemporal choices. Consequently, the cyclical volatilities of aggregate variables are also affected. As a numerical exercise, we quantify how increased life expectancy has impacted Canadian business cycle fluctuations over the past forty years. The results indicate that the fluctuations in physical capital, human capital, and consumption all decrease as life expectancy increases. On the other hand, the fluctuation of hours worked, output, and trade balance ratio are found to increase with life expectancy.
Keywords: E32; F41; J11; 330; Business cycles; Life expectancy; Finite lifetimes; Small open economy